Peptidoglycan enzymes of Francisella: Roles in cell morphology and pathogenesis, and potential as therapeutic targets - Bachert, Beth A.; Bozue, Joel A. (Frontiers in Microbiology, 2023)
Peptidoglycan, found within the cell wall of bacteria, is a structure critical for maintaining cell morphology and providing a protective barrier in diverse environments. Peptidoglycan is a remarkably dynamic structure that is constantly remodeled during cell growth and division by various peptidoglycan enzymes. Numerous peptidoglycan enzymes have been characterized from diverse bacteria and are highly sought after as targets for therapeutics. However, very little is known about these enzymes within the biothreat agent Francisella tularensis. As the causative agent of tularemia, F. tularensis is classified as a category A biothreat pathogen, in part due to its low infectious dose and lack of FDA-approved vaccine. Many bacterial species encode multiple peptidoglycan enzymes with redundant functions that allow for compensation if one of the enzymes are inactivated. In contrast, F. tularensis appears to lack this redundancy, indicating peptidoglycan enzymes may be completely essential for growth and could be exploited as targets for medical countermeasures. Indeed, several peptidoglycan enzymes in F. tularensis have been shown to play important roles in cell division, cell morphology, virulence, and modulation of host response. The aim of this review is to summarize findings from the current literature on peptidoglycan enzymes present in Francisella and discuss areas where future research efforts might be directed. We conclude that Francisella harbors a distinct set of peptidoglycan enzymes important for cell growth and virulence and represent potentially valuable targets for the development of novel therapeutics.